2020
DOI: 10.3390/ijerph17113982
|View full text |Cite
|
Sign up to set email alerts
|

Geo-Epidemiology of Malaria at the Health Area Level, Dire Health District, Mali, 2013–2017

Abstract: Background: According to the World Health Organization, there were more than 228 million cases of malaria globally in 2018, with 93% of cases occurring in Africa; in Mali, a 13% increase in the number of cases was observed between 2015 and 2018; this study aimed to evaluate the impact of meteorological and environmental factors on the geo-epidemiology of malaria in the health district of Dire, Mali. Methods: Meteorological and environmental variables were synthesized using principal component analysis and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 39 publications
5
41
1
Order By: Relevance
“… 37 Additionally, six (6%) studies used the total-sets analysis based on Bayesian information criterion (BIC) statistic to identify the optimal variable combination. Principal component analysis was employed by eight (8%) studies to reduce dimensions and avoid collinearities in environmental factors, 38 39 meteorological factors 38 40 and household demographics. 32 33 41–43 The Bayesian stochastic search was used by three (3%) studies to identify covariates with the highest inclusion probability.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Additionally, six (6%) studies used the total-sets analysis based on Bayesian information criterion (BIC) statistic to identify the optimal variable combination. Principal component analysis was employed by eight (8%) studies to reduce dimensions and avoid collinearities in environmental factors, 38 39 meteorological factors 38 40 and household demographics. 32 33 41–43 The Bayesian stochastic search was used by three (3%) studies to identify covariates with the highest inclusion probability.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies in the literature have shown that rainfall and humidity increase the risk of malaria by developing suitable breeding sites and increasing mosquito density [ 30 , 33 , 34 ]. Studies show the persistence of malaria transmission despite the intensification of control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Lagged SMI selection Several studies have observed a lag between malaria time series and meteorological data time series [24,25,26]. In view of this, we decided to investigate the time lag (in weeks) between the time series of weekly malaria cases and the time series of SMIs.…”
Section: Temporal Analysesmentioning
confidence: 99%
“…SMC or LLIN distribution). Indeed, as numerous studies have shown, malaria incidence at the local level is heterogeneous and associated with spatio-temporal clusters [12,13,14] that are likely to maintain transmission during low-risk periods and, consequently, to increase transmission during high-risk periods [15,16,17]. Identifying these clusters can therefore help to improve the fight against malaria and to anticipate future outbreaks.…”
Section: Introductionmentioning
confidence: 99%